(untitled) (African Multidisciplinary Journal of Research, 2025)
This study examined the role of coordinated social media as a strategic messaging platform in the 2024 Gen Z uprising in Kenya, specifically focusing on the anti-Finance Bill protests that fundamentally transformed political mobilization patterns in the country. Using a mixed-methods approach, this research analyzes how platforms like TikTok, Twitter (X), and Instagram facilitated political mobilization and advocacy among Kenyan youth, creating what scholars’ term "digital-first political expression" that bypassed traditional gatekeeping mechanisms. The study reveals that unlike traditional opposition movements characterized by elite-driven leadership, ethnic mobilization, and hierarchical organization, the 2024 Gen Z uprising demonstrated unprecedented organizational innovation through leaderless structures, distributed coordination across multiple digital platforms, and issue-based mobilization that transcended traditional ethnic and generational boundaries. The findings demonstrate that coordinated digital messaging created network society forms of political organization, where horizontal communication networks enabled direct political participation without traditional intermediaries, ultimately forcing government policy reconsideration through grassroots digital activism. The movement’s success in utilizing platform-specific strategies—Twitter for real-time coordination, TikTok for viral content creation, and WhatsApp for logistics—represents a paradigmatic shift from mass society to network society politics. The research reveals diverse motivations for participation, including genuine rights advocacy, accountability-centered engagement, and digitally-mediated collective action that challenged conventional co-optation strategies. These findings underscore the emergence of post-ethnic political mobilization among Kenya’s digital natives and highlight how the pervasive influence of social media as a strategic platform fundamentally disrupted traditional political structures while establishing new paradigms for democratic participation in twenty-first-century Africa.